Spatial variations on methane emissions from Zoige alpine wetlands of Southwest China - Chen, Huai; Wu, Ning; Gao, Yongheng; Wang, Yanfen; Luo, Peng; Tian, Jianqing (Science of The Total Environment, 2009)
This study was aimed to understand the spatial variation of CH4 emissions from alpine wetlands in Southwest China on a field-scale in two phenological seasons, namely the peak growing season and the spring thaw. Methane emission rates were measured at 30 plots, which included three kinds of environmental types: dry hummock, Carex muliensis and Eleocharis valleculosa sites. There were highly spatial variations of methane emissions among and within different environmental types in both phenological seasons. Mean methane emission rates ranged from 1.1 to 37.0 mg CH4 m(-2) h(-1) in the peak growing season and from 0.004 to 0.691 mg CH4 m(-2) h(-1) in the spring thaw. In the peak growing season, coefficients of variation (CV) averaged 38% among environmental types and 64% within environmental types; while in the spring thaw, CV were on the average 61% among environmental types and 96% within environmental types. The key influencing factors were the standing water table and the plant community height in the peak growing season, while in the spring thaw, no significant correlations between factors and methane emissions were found. (C) 2008 Elsevier B.V. All rights reserved